Single-strand conformational polymorphism analysis of a common single nucleotide variation in WRAP53 gene, rs2287499, and evaluating its association in relation to breast cancer risk and prognosis among Iranian-Azeri population - Sedaie Bonab, Aida; Pouladi, Nasser; Hosseinpourfeizi, Mohammad Ali; Ravanbakhsh Gavgani, Reyhaneh; Dehghan, Roghayeh; Azarfam, Parvin; Montazeri, Vahid; Fakhrjou, Ashraf (Medical oncology (Northwood, London, England), 2014)
The WRAP53 (WD40-encoding RNA antisense to p53) gene encodes an antisense RNA, essential for p53 stabilization and induction upon DNA damage. Single nucleotide polymorphisms (SNPs) in WRAP53 have been associated with risk of cancer, which strengthens the role of WRAP53 in the pathogenesis of human malignancies. In fact, WRAP53 has been considered as a candidate cancer susceptibility gene. Accordingly, we performed a study to examine the association of a frequent genetic variation in WRAP53 , rs2287499 (C/G), with breast cancer risk and prognosis among Iranian-Azeri population. A case–control association study, including 206 cases and 203 controls from Iranian-Azeri population, was conducted. Genomic DNA was extracted from peripheral blood and tumor samples by salting-out method. SNP genotyping was carried out by polymerase chain reaction-based single-strand conformational polymorphism (PCR-SSCP) technique. The sequence variation of SSCP banding patterns was determined by sequencing. The collected data were analyzed through statistical package for the social sciences software, using Chi-square ( χ 2 ) or Fisher’s exact tests, with a significance level of 0.05. No significant differences in the allele and genotype frequencies between cases and controls were detected. Similarly, no significant associations between genotypes and clinicopathological data were observed. Concisely, no significant overall associations between rs2287499 and breast cancer risk and prognosis were detected in the studied population. The rs2287499 SNP is not associated with breast cancer predisposition in Iranian-Azeri women; it also cannot be used as a molecular biomarker to predict breast cancer prognosis in Iranian-Azeri population.